Implementasi Media Audio Visual Interaktif dalam Elemen Akidah Akhlak pada Mata Pelajaran PAI dan Budi Pekerti di Kelas VIII SMP Muhammadiyah 3 Purwokerto - Waluyo , Abror (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Technological advancements have brought significant changes to the field of education, including in the teaching of Akidah Akhlak (Faith and Morality), which is often perceived as abstract and unengaging by students. This study aims to analyze the implementation of interactive audio-visual media in Akidah Akhlak learning for Grade VIII students at SMP Muhammadiyah 3 Purwokerto, identify its impact on students' understanding, and determine the supporting and inhibiting factors in its application. The research employs a qualitative method with a field research approach. Data was collected through observation, in-depth interviews with Islamic Education teachers, the school principal, and students, as well as supporting documentation.The implementation process involves three main stages: (1) planning, including learning objectives, learning pathways, and teaching modules; (2) execution, such as the use of videos, animations, and interactive discussions; and (3) evaluation. The findings indicate that interactive audio-visual media, such as animated videos and digital presentations, effectively visualize abstract concepts of Akidah Akhlak, making them easier to comprehend. Students appeared more enthusiastic and engaged in learning. However, limitations in facilities, such as the insufficient number of projectors and teachers' readiness in operating the equipment, posed challenges that need to be addressed. Overall, the application of this media enhances students' interest and understanding of the values of faith and morality. Based on data analysis using the aforementioned techniques, it can be concluded that the Implementation of Interactive Audio-Visual Media in the Akidah Akhlak Element for Grade VIII at SMP Muhammadiyah 3 Purwokerto is well-aligned, although still in the adjustment phase